Pengembangan Game Dengan Menggunakan Game Engine Game Maker - Teguh Martono, Kurniawan (Jurnal Sistem Komputer, 2015)
Computer is one part that can not be separated in human life at this time. The use of computer technology penetrated in all areas of health, education, military and trade. One of the effects of perkembanagn computer technology is in the field of entertainment, namely games. Game is one of the multimedia applications that can be used for various purposes such as education, entertainment, or for simulation. The development of a game requires methods and tools. Various methods can be used in deploy, one method that can be used is to use the method of multimedia development. Tool that can be used in the development of the game is to use the game maker. This tool is one tool that can be learned in a short time. Use game tool maker in game development can be used for game development beginner. This is because the language used in the game maker uses symbols are easily understood by the user. The language used in the tool maker game is to use GML language or the game maker.